Reduction of carbamylated albumin by extended hemodialysis. Issue 4 (21st June 2016) - Perl, Jeffrey; Kalim, Sahir; Wald, Ron; Goldstein, Marc B.; Yan, Andrew T.; Noori, Nazanin; Kiaii, Mercedeh; Wenger, Julia; Chan, Christopher; Thadhani, Ravi I.; Karumanchi, S. Ananth; Berg, Anders H.
Abstract: Introduction Among conventional hemodialysis (CHD) patients, carbamylated serum albumin (C‐Alb) correlates with urea and amino acid deficiencies and is associated with mortality. We postulated that reduction of C‐Alb by intensive HD may correlate with improvements in protein metabolism and cardiac function. Methods One‐year observational study of in‐center nocturnal extended hemodialysis (EHD) patients and CHD control subjects. Thirty‐three patients receiving 4‐hour CHD who converted to 8‐hour EHD were enrolled, along with 20 controls on CHD. Serum C‐Alb, biochemistries, and cardiac MRI parameters were measured before and after 12 months of EHD. Findings EHD was associated with reduction of C‐Alb (average EHD change −3.20 mmol/mol [95% CI −4.23, −2.17] compared to +0.21 [95% CI −1.11, 1.54] change in CHD controls, P < 0.001). EHD was also associated with increases in average essential amino acids (in standardized units) compared to CHD (+0.38 [0.08, 0.68 95%CI]) vs. −0.12 [−0.50, 0.27, 95% CI], P = 0.047). Subjects who reduced C‐Alb more than 25% were found to have reduced left ventricular mass, increased urea reduction ratio, and increased serum albumin compared to nonresponders, and % change in C‐Alb significantly correlated with % change in left ventricular mass. Discussion EHD was associated with reduction of C‐Alb as compared to CHD, and reduction of C‐Alb by EHD correlates with reduction of urea. Additional studies are needed to test whether reduction of C‐Alb by EHD also correlates with improved clinical outcomes.